Identification of Process-Based Limit Stress States Applying a Stretch-Bending-Test - Hezler, Christian; Merklein, Marion; Hecht, Joachim; Griesbach, Bernd (Key Engineering Materials, 2012)
The evaluation of forming simulation by using the forming limit curve has only limited validity if it is applied on car body components with non-linear strain paths. If modern high strength materials are used, the forming limit criteria can also provide invalid predictions. Especially high strength multiphase steels show a specific behaviour in forming, necking and crack initiation. If bending loads are applied to these materials, the onset of cracking occurs partially not within the range of the forming limit curve (FLC). The stress limit indicates the failure beginning more accurate. It is independent of the forming history and should be less sensitive to the behaviour of high strength steels. In the post processing of a simulation it could be used similar to the forming limit. A limit curve applied on the in-plane-stress-diagram of an analysed component defines areas that are more vulnerable for cracking. The required stress limit curve will be obtained in this research by applying a stretch-bending-test. It is selected in order to reach loads, which are comparable to the forming process in the components' production. The forming state that is affecting the specimen is a combination of bending and stretching load. Different load conditions can be applied at the test by altering the stamp-radius and the specimen geometry. Since stresses cannot be measured directly in the experiment, the test is modelled in the simulation where the stresses can be calculated for a given material model. Finally the stress limit criterion was applied on the test parts' stress distribution diagram. Occurring stresses above the stress limit curve are displayed on the simulation. Thereby it is possible to show a good correlation in critical areas between the failure prediction in the simulation and occurring rupture on the test component. © (2012) Trans Tech Publications.
LFT Import::2019-07-29 (1786)
Keywords: High strength steels; Process-orientated characterisation; Stress limit criteria; Stretchbending- test